Primary metastatic breast cancer in the era of targeted therapy: prognostic impact and the role of breast tumour surgery - Barinoff, Jana; Schneeweiss, Andreas (European journal of cancer, 2017)
Background: Except for meeting the individual palliative need, the benefit of breast surgery in primary metastatic breast cancer (PMBC), also known as de novo metastatic breast cancer, on long-term outcomes remains controversial. Twenty-four hundred and one patients with metastatic breast cancer, enrolled between 2000 and 2011 in two prospective non-interventional studies on targeted therapy, were screened with respect to this question. Methods: One study investigated trastuzumab therapy for human epidermal growth factor receptor 2 (HER2)-positive metastatic breast cancer in addition to mainly first-line chemotherapy. The other observed bevacizumab added to chemotherapy as first-line treatment for mostly HER2-negative disease. Results: Five-hundred and seventy (24%) patients presented with PMBC, and valid information on resection of the primary tumour was available for 568 women. Out of these, 426 (75%) underwent local resection. The latter group was characterised by less overall metastatic burden and a lower proportion of T4 tumours. No major differences were observed with respect to age, hormone receptor and HER2 status, visceral disease and performance status. Numerically, the surgery group showed a slightly favourable progression-free survival (PFS, medians: 13.6 versus 11.8 months; P = 0.18) and overall survival (OS, 34.1 versus 31.7; P = 0.23). However, in multivariable analysis, including all other univariably significant parameters, no trend for better outcome after surgery remained detectable, neither for PFS (hazard ratio 0.99; P = 0.92) nor for OS (0.95; P = 0.71). Conclusions: Our findings suggest no major survival benefit for local resection in the overall PMBC population treated with modern targeted therapies. However, further analyses are warranted to define specific risk groups, which may benefit from surgical removal of the primary.